2004
DOI: 10.1080/13803390490510077
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Reasoning in Primary Progressive Aphasia: Further Differentiation from Alzheimer's Disease and the Behavioral Presentation of Frontotemporal Dementia

Abstract: Primary Progressive Aphasia (PPA) is a clinical dementia syndrome characterized by the gradual dissolution of language without impairment of other cognitive domains for at least the first 2 years of illness (M.-M. Mesulam, 1982, 2001). It is difficult to demonstrate the integrity of nonlanguage domains in PPA because most neuropsychological tests of memory, reasoning, and attention require language competence for their performance. In the present study, reasoning and cognitive flexibility were tested nonverbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 21 publications
1
45
0
2
Order By: Relevance
“…Therefore, the low scores on some nonlanguage tests were attributed to interference from the language impairment. PPA patients showed relatively less impairment in CERAD Word List Recognition, Visual Target Cancellation, JLO, and the Visual-Verbal Test (Wicklund et al, 2004), representing tests of memory, visuospatial functions, and reasoning and executive functions, respectively. Normal controls showed no impairments on any of the neuropsychological tests.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the low scores on some nonlanguage tests were attributed to interference from the language impairment. PPA patients showed relatively less impairment in CERAD Word List Recognition, Visual Target Cancellation, JLO, and the Visual-Verbal Test (Wicklund et al, 2004), representing tests of memory, visuospatial functions, and reasoning and executive functions, respectively. Normal controls showed no impairments on any of the neuropsychological tests.…”
Section: Methodsmentioning
confidence: 99%
“…A greater deficit in naming verbs than naming nouns is associated with nonfluent, agrammatic forms of PPA . Verb processing deficits can also occur in AD, but the deficits are linked to impaired processing of the semantic rather than the syntactic information carried by verbs (Grossman et al 1996;Kim and Thompson 2004).Neuropsychological studies that directly compared patients with clinically diagnosed PPA, bvFTD, and AD have shown that those with PPA have relatively preserved reasoning and episodic memory compared with the other two groups (Wicklund et al 2004(Wicklund et al , 2006. Furthermore, functional ability reflected in activities of daily living (ADL) is better preserved in patients with PPA than in the other two groups when duration of illness is controlled (Wicklund et al 2007).…”
mentioning
confidence: 99%
“…It may often be diffi cult to confi rm normal function in other cognitive when signifi cant language defi cits are present. Modifi cation of standard testing paradigms to reduce their dependence on language skills can be useful (Wicklund et al 2004). Defi cits in other cognitive domains eventually emerge after the initial few years, but the language dysfunction remains the most salient feature and advances most rapidly, throughout the course of the illness (Mesulam 2003).…”
Section: Clinical Presentation and Evolutionmentioning
confidence: 99%